2017
DOI: 10.1111/jgh.13533
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of microRNA‐26a and microRNA‐148a in gastric cancer

Abstract: These findings supported miR-26a and miR-148a could serve as potential prognostic biomarkers for GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…We used bioinformatics methods to identify a conserved miR-26 binding site in the 3ʹ-UTR of HOXC9 mRNA. Since miR-26a, a miR-26 family member, was downregulated in GC, we suspected that the loss of miR-26a expression leads to HOXC9 upregulation in GC [12]. The present results suggest the presence of a miR-26a/HOXC9 axis in GC.…”
Section: Discussionsupporting
confidence: 57%
“…We used bioinformatics methods to identify a conserved miR-26 binding site in the 3ʹ-UTR of HOXC9 mRNA. Since miR-26a, a miR-26 family member, was downregulated in GC, we suspected that the loss of miR-26a expression leads to HOXC9 upregulation in GC [12]. The present results suggest the presence of a miR-26a/HOXC9 axis in GC.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, lower miR-26a expression was significantly associated with diffuse type GC, but the relationship between miR-26a and Lauren's classification is controversial. While higher miR-26a expression was reported to be associated with diffuse type GCs 35 , others reported downregulated miR-26a in poorly differentiated GCs 36 . More research is needed to clarify how miRNA functions in tumorigenesis according to Lauren's classification.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Xu et al found that miR-148a functioned to suppress metastasis and served as a prognostic indicator in triple-negative breast cancer 20. Downregulation of miR-148a was significantly associated with shorter overall survival of gastric cancer patients 25. In contrast, decreased expression of miR-148a was found to predict poor prognosis in ovarian cancer and to be associated with tumor growth and metastasis 26.…”
Section: Discussionmentioning
confidence: 99%